Sembrar y producir en el hogar: una manera de fomentar la seguridad agroalimentaria - Pedro Monasterio; Jacinto Tablante; Waner Maturet; Fanny Sanchez; Tony Yépez (INIA Divulga, 2017)
A fortress for urban agricultural production. The emigration of the population to the cities in search of better living conditions has increased the demand for horticultural products. This circumstance strengthens the use of small spaces, which form large production areas and with many advantages; Planting horticultural plants in small spaces, such as flower pots in windows, gardens, edges of recreational areas and in recycling containers or jugs, is common in homes with ornamental plants (Photo 1).This way of producing works as a school for our children, since, by carrying out the activities of preparing the soil, seeds in an artisan way, sowing and irrigation in the company of the family environment, it contributes to the training of new farmers; which are the seed of the agricultural future of the country.Teaching urban agriculture is easy and fun when done as a family, because it does not require much time or space, it allows a beautification of the home and makes it productive, even for community interaction with educational centers, this being the main advantage of this way of producing food.